Trauma : explorations in memory - Caruth, Cathy, 1955- (Johns Hopkins University Press, 1995)
Contributions by: Georges Bataille, Harold Bloom, Laura Brown, Cathy Caruth, Kai Erikson, Shoshana Felman, Henry Krystal, Claude Lanzmann, Dori Laub, Kevin Newmark, Onno van der Hart, and Bessel van der Kolk. Interviews with: Robert Jay Lifton, Gregg Bordowitz, Douglas Crimp, and Laura Pinsky